2015
DOI: 10.1002/14651858.cd010756.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids for the management of cancer-related pain in adults

Abstract: The evidence for the efficacy of corticosteroids for pain control in cancer patients is weak. Significant pain relief was noted in some studies, albeit only for a short period of time. This could be important for patients with poor clinical status. Further trials, with increased numbers of participants, are needed to evaluate the safety and effectiveness of corticosteroids for the management cancer pain in adults, and to establish an ideal dose, duration of therapy and route of administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 49 publications
1
35
0
3
Order By: Relevance
“…If the pain is not sufficiently controlled a weak opioid can then be introduced, and subsequently a strong opioid. Steroids have been shown to reduce cancer-related pain [103]. For neuropathic pain, amitriptyline, sodium valproate or gabapentin may be administered [104].…”
Section: Palliation: Pain Relief Nutrition and Jaundicementioning
confidence: 99%
“…If the pain is not sufficiently controlled a weak opioid can then be introduced, and subsequently a strong opioid. Steroids have been shown to reduce cancer-related pain [103]. For neuropathic pain, amitriptyline, sodium valproate or gabapentin may be administered [104].…”
Section: Palliation: Pain Relief Nutrition and Jaundicementioning
confidence: 99%
“…Corticosteroids are commonly used in management of cancer pain however there is limited quality data supporting their efficacy for this purpose (1,2). A recent Cochrane systematic review in 2015 evaluated the efficacy of corticosteroids in treating cancer-related pain in adults (3). In this review there were fifteen studies that met the inclusion criteria, with a total of 1926 participants enrolled.…”
Section: Corticosteroids As Co-analgesics With Opioids For Cancer Relmentioning
confidence: 99%
“…With regard to the treatment of pain, a randomized controlled trial found no analgesic effect of corticosteroids in cancer patients taking opioids [17], whereas two studies have showed an analgesic effect [19], or temporarily increased pain control [16]. A meta-analysis in a recently published Cochrane review concluded that corticosteroids could provide a mean reduction of pain intensity of 0.84 on a numeric rating scale (NRS 0–10) (confidence interval, (CI) -1.38 to -0.3) after one week of treatment [20]. The mechanisms of action are not well defined, but are thought to be mediated by their anti-inflammatory effects.…”
Section: Introductionmentioning
confidence: 99%